Hypothermia in VGKC antibody-associated limbic encephalitis. - Jacob, S; Irani, SR; Rajabally, Y; Grubneac, A; Walters, R; Yazaki, M; Clover, L; Vincent, A (2008)
Voltage-gated potassium channel antibody (VGKC-Ab)-associated limbic encephalitis (LE) is a recently described syndrome that broadens the spectrum of immunotherapy-responsive central nervous system disorders. Limbic encephalitis is typically characterised by a sub-acute onset of disorientation, amnesia and seizures, but the clinical spectrum is not yet fully defined and the syndrome could be under-diagnosed. We here describe the clinical profile of four patients with VGKC-Ab-associated LE who had intermittent, episodic hypothermia. One of the patients also described a prodrome of severe neuropathic pain preceding the development of limbic symptoms. Both of these novel symptoms responded well to immunosuppressive therapy, with concurrent amelioration of amnesia/seizures.